Morphology control synthesis of nano rods and nano ovals CaCO3 particle systems. Issue 9 (15th July 2020) - Akhtar, Khalida; Yousafzai, Saniya
Abstract: Uniform fine particles of CaCO3 in nano rod and nano oval morphology were synthesized by carbonation and controlled precipitation methods. For this, commercially available cheap source of quicklime was used as a starting reactant against different precipitants, i.e., CO2, Na2 CO3 and (NH4 )2 CO3 . The effect of precipitating agent and various other experimental conditions on particle size and shape was systematically studied. The reaction parameters were extensively optimized for the generation of novel morphologies of CaCO3 ultrafine particle systems in a reproducible manner. The synthesized material was characterized by SEM, X-ray diffraction (XRD), FT-IR, and TGA/DTA techniques. Cubic and spherical shape particles were produced by using Na2 CO3 and (NH4 )2 CO3 respectively as a precipitating agents. Agitation of the reaction mixture by sonication and mechanical stirring affected the particle uniformity. Furthermore, unique novel morphologies of CaCO3 particles in rod and oval shapes were synthesized from carbonation of Ca(OH)2 at low temperature with a flow rate of 0.6 L/min in the absence and presence of K2 SO4 respectively. The XRD results showed single phase formation of calcite for both morphologies, while the preferred orientation of XRD peak was observed at (104) plane. The calculated activation energy showed thermal stability of the synthesized oval shape CaCO3 particles over the rod shape particle morphology. Graphical Abstract: